Analisis Penerapan Etika Bisnis Islam dalam Pelaksanaan Penjualan Sapi pada CV Limusin Group Bondowoso - Istiqomah, Darul; Bramayudha, Airlangga (Journal of Islamic Economics Studies and Practices, 2024)
This research aims to analyze the Application of Islamic Business Ethics in the Implementation of Cattle Sales at the Cv Limusin Group Bondowoso in knowing Islamic business ethics and the principles of Islamic business ethics. This research uses qualitative research methods to collect data through interviews with various stakeholders, including managers, marketing staff, finance, production, personnel and company customers. The data analysis technique begins with the results of interview and interview data, then documentation in the form of evidence that matches the data regarding the matter in the form of transcripts. The data validation technique uses data triangulation. The results of the research explain several obstacles faced, such as the need for halal certification, monitoring production processes, and customer education. However, various strategies have been proposed to overcome these obstacles, such as employee training, cooperation with religious authorities, and close monitoring during the production process. Although there are still challenges that need to be overcome, implementing Islamic business ethics has provided benefits for companies, including customer trust and improved reputation. Therefore, the conclusion is that with the right commitment and appropriate strategy businesses can successfully implement Islamic business ethics in their operations.